Analysis of Fouling Factors on Heat Transfer in Shell and Tube Heat Exchangers Type 1-2 Pass - Aditya, Yudi; Irwansyah; Weriono; Indra Hermawan; Idris, Muhammad (Universitas Medan Area, 2024)
A heat exchanger is a device that is used to change the temperature or fluid phase by absorbing or releasing heat between the hot fluid and the cold fluid. One type of heat exchanger that is most widely used in industry is shell and tube. Optimal heat exchanger performance has an important role to support production stability in various industries. The performance of shell and tube heat exchangers is affected by fouling factors which are the formation of deposits on the surface of the heat exchanger which can inhibit heat transfer and increase the resistance to fluid flow in the heat exchanger. After analysis, it is known that the mass flow rate of the flue gas is 0.06523 kg/s, the effectiveness of the heat exchanger is 66.837%, the overall gross area is 3.317350717 m2, and the effective heat transfer area is 2.211567145 m2.